Laboratory Techniques Used to Diagnose Constitutional Platelet Dysfunction - Ibrahim-Kosta, Manal; Alessi, Marie-Christine; Hezard, Nathalie (Hämostaseologie, 2020)
Platelets play a major role in primary hemostasis, where activated platelets form plugs to stop hemorrhaging in response to vessel injuries. Defects in any step of the platelet activation process can cause a variety of platelet dysfunction conditions associated with bleeding. To make an accurate diagnosis, constitutional platelet dysfunction (CPDF) should be considered once von Willebrand disease and drug intake are ruled out. CPDF may be associated with thrombocytopenia or a genetic syndrome. CPDF diagnosis is complex, as no single test enables the analysis of all aspects of platelet function. Furthermore, the available tests lack standardization, and repeat tests must be performed in specialized laboratories especially for mild and moderate forms of the disease. In this review, we provide an overview of the laboratory tests used to diagnose CPDF, with a focus on light transmission platelet aggregation (LTA), flow cytometry (FC), and granules assessment. Global tests, mainly represented by LTA, are often initially performed to investigate the consequences of platelet activation on platelet aggregation in a single step. Global test results should be confirmed by additional analytical tests. FC represents an accurate, simple, and reliable test to analyze abnormalities in platelet receptors, and granule content and release. This technique may also be used to investigate platelet function by comparing resting- and activated-state platelet populations. Assessment of granule content and release also requires additional specialized analytical tests. High-throughput sequencing has become increasingly useful to diagnose CPDF. Advanced tests or external research laboratory techniques may also be beneficial in some cases.
Keywords: constitutional platelet dysfunction; diagnosis; light transmission aggregometry; granule deficiency; flow cytometry